1969
DOI: 10.12669/pjms.303.5354
|View full text |Cite
|
Sign up to set email alerts
|

The clinical & neurophysiological study of leprosy

Abstract: Objectives: The aim of this study was to evaluate neurological and neurophysiological features of leprosy. Methods: Seventy seven hospitalized leprosy patients (52 male, 25 female) were examined neurological and neurophysiologically between 2010 and 2012. Standard procedures were performed for evaluating sensory and motor conduction studies to all patients. Motor studies were carried out on median, ulnar, tibial and common peroneal nerves. Sensory studies were carried out on median, ulnar and sural nerves. Sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus as a single test, electrophysiology is better, but combination of clinical examination and electrophysiology is the best approach. 21 When sympathetic skin response (SSR) was combined with routine electrophysiology, features of nerve dysfunction identified was 81.8%, as it will identify small fiber involvement. In the current study, SSR was not done, as it required more expertise and time consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Thus as a single test, electrophysiology is better, but combination of clinical examination and electrophysiology is the best approach. 21 When sympathetic skin response (SSR) was combined with routine electrophysiology, features of nerve dysfunction identified was 81.8%, as it will identify small fiber involvement. In the current study, SSR was not done, as it required more expertise and time consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Cabalar et al, in their study, found neurophysiological abnormalities in 40% of leprosy patients without evident nerve involvement. 34 In the literature, there are studies indicating a high prevalence of defects in vasomotor responses of both leprosy patients as their household contacts. 13 , 36 …”
Section: Discussionmentioning
confidence: 99%